A novel failure criterion based upon forming limit curve for thermoplastic composites. (1st December 2020) - Wang, Zhen; Zhang, Wenwu; Luo, Quantian; Zheng, Gang; Li, Qing; Sun, Guangyong
Abstract: This study aims to explore failure mechanism and failure criteria of carbon fiber reinforced polypropylene (CFRPP) by presenting a novel notch-shaped design of specimens with two different fiber orientations (0/90)4 and (+45/-45)4 subject to stamping process under room temperature. Two forming limit curves/diagrams (FLCs/FLDs) were established based upon the minor strain and major strain, as well as the developed equivalent fiber strain combined with a ratio of minor to major strain ( S R ), respectively. A novel notch-shaped design enables to minimize the influence of fiber orientation on failure modes and FLC of CFRPP effectively. Not only did the equivalent fiber strain based FLC reflect the failure mode in terms of a certain S R value, but also showed the failure strain on fiber bundles quantitatively. Finite element (FE) models involving the new failure criteria (FLC) were developed on the basis of the experimental results. It was found that such a new FE model is able to better predict the results than those with the conventional maximum strain or maximum stress failure criteria. The difference in failure behaviors among these three failure criteria (i.e. FLC, maximum strain and maximum stress) was compared. The history of failure evolution and potential damage status of typical specimens were further analyzed through the FE model. The results indicated that the new FLC failure criteria can be used for the failure assessment in CFRPP structures. This study is anticipated to provide a guideline for further investigation into failure mechanism and failure criteria of thermoplastic composites under different service conditions.